Communication in sport management - Pedersen, Paul Mark (Routledge, 2025)
This book presents cuttingedge perspectives on Communication in Sport Management, a core component of contemporary sport business. Featuring the work of leading sport scholars from around the world, this book explores seven key themes in sport communication: engagement, technology, branding, publicity, finance, health, and crisis communication. Drawing on multidisciplinary perspectives, including communication and media studies, management, finance, and sociology, this book examines cuttingedge topics such as digital sport fandom, online abuse, communication in esports, developing athlete brands, and managing scandal. Offering an important snapshot of the state of the art in sport communication, this book is fascinating reading for any advanced student, researcher, policy maker, or practitioner working in sport business and management, sport media, digital media, public relations, or broadcasting.
Keywords: Communication in sports.; Soccer -- Social aspects.; elektronické knihy; electronic books